2005
DOI: 10.1007/s11255-005-0918-5
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Recovery Prediction in Azoospermic Patients Using Doppler Ultrasonography

Abstract: Testicular Power Doppler assessment showed that patients with obstructive azoospermia have better blood flow than patients with non-obstructive azoospermia, and power Doppler is able to predict sperm recovery in azoospermic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
(27 reference statements)
1
10
0
2
Order By: Relevance
“…A noninvasive technique helping to predict the chance of obtaining spermatozoa at TESE would be beneficial. Several studies have assessed the efficacy of color or power Doppler sonographic mapping of NOA testes to predict the presence of spermatogenic foci . Foresta et al in a study of 12 NOA subjects with color and power Doppler US analyzed the presence of intratesticular vessels by dividing each testis into medial or lateral, anterior or posterior side of the cranial, middle, and caudal thirds .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A noninvasive technique helping to predict the chance of obtaining spermatozoa at TESE would be beneficial. Several studies have assessed the efficacy of color or power Doppler sonographic mapping of NOA testes to predict the presence of spermatogenic foci . Foresta et al in a study of 12 NOA subjects with color and power Doppler US analyzed the presence of intratesticular vessels by dividing each testis into medial or lateral, anterior or posterior side of the cranial, middle, and caudal thirds .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the efficacy of color or power Doppler sonographic mapping of NOA testes to predict the presence of spermatogenic foci. [6][7][8][9][10][11] Foresta et al in a study of 12 NOA subjects with color and power Doppler US analyzed the presence of intratesticular vessels by dividing each testis into medial or lateral, anterior or posterior side of the cranial, middle, and caudal thirds. 8 The authors concluded that the presence of blood vessels, especially in peripheral regions, might indicate the possible presence of residual spermatogenic foci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite correlating more closely with impaired spermatogenesis than does FSH, inhibin‐B level is not diagnostic (Vernaeve, Brugnon, & Tournaye, ). Doppler ultrasonography was recently used to correlate testicular blood flow with successful sperm recovery in azoospermic men, but whether its results are definitive remains under investigation (Souza, Cunha‐Filho, Fagundes, Freitas, & Passos, ). The limited sample did not allow us to define any clinically good positive prognostic factor among those analysed, and it was clear that these indicators were related to the diversity of the subjects studied in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Several candidate clinical markers intended to predict the presence of sperm within the testis have been proposed including testis size, FSH, serum testosterone, inhibin B, genetic profiles (karyotype, Y-microdeletions) and blood flow patterns within the testis on Doppler studies. [15][16][17][18][19] Unfortunately, none have demonstrated consistent clinical reliability compared with an in-depth testicular tissue analysis and sampling using the surgical microscope. Even the pathology on a previous diagnostic testicular biopsy (usually a randomly sampled tissue biopsy) does not definitively predict whether sperm are present or absent throughout the remaining of testis among men with non-obstructive azoospermia.…”
Section: Introductionmentioning
confidence: 99%